Cardiac Rehabilitation in Women and Men after an Acute Myocardial Infarction - Elizabeth Sellén Sanchén; Vivian Gil García; Nordan Pedroso Almarales; Yunior Rodríguez López; Joaquín Sellén Crombet (Revista Finlay)
Background: cardiovascular rehabilitation favors the recovery of patients suffering from acute myocardial infarc-tion. Objective: to characterize cardiovascular rehabilitation in women and men with a first uncomplicated acute myo-cardial infarction with ST-segment elevation. Methods: a descriptive and cross-sectional study was carried out at the Cardiovascular Care Center of the Manuel Ascunce Domenech Teaching Clinical Surgical Provincial Hospital in Camagüey in the period from September 2015 to September 2016. The sample consisted of 65 patients. who underwent a stress test and echocardiogram before discharge and 6 weeks after rehabilitation. Survival was evaluated at five years. Symptom-limited maximal stress test was performed to determine risk stratification, functional capacity, activity prescription and provide information to the patient. Results: there was a higher incidence of rehabilitated infarction in males, the most affected age group was 50-59 years, and arterial hypertension was the predominant cardiovascular risk factor. There was notable improvement in the ergometric and hemodynamic parameters after 6 weeks of rehabilitation. The hypertensive reaction and dysp-nea decreased in most cases at the end of the study. The patients who began the study improved their functional class 6 weeks after rehabilitation and there was an increase in the low risk category at the expense of moderate risk. Five-year survival was 89.9 %. Conclusions: a significant improvement of clinical and ergometric parameters was obtained, as well as the return to daily tasks in the patients who participated in the program. Women received fewer benefits from this program than men.